Development of Three-Dimensional Scour below Pipelines in Regular Waves - Yehui Zhu; Liquan Xie; Tsunming Wong; Tsung-Chow Su (Journal of Marine Science and Engineering, 2022)
The three-dimensional scour beneath a partially-buried pipeline in regular waves was visualized using a miniature camera installed in a transparent pipeline. The scour mechanism was analyzed based on the results. Scour development was observed to start at the upstream edge of the span shoulder when the flow in the span headed downstream. The nearby sediment scoured quickly, and a new scour front formed, which can be attributed to the deflected flow entering the scour hole. The new scour front retreated gradually. The end of the original scour front deformed and moved downstream, probably due to the enhanced seepage flow near the edge of the span shoulder. After that, the new scour front extended to the downstream interface of the sediment and the pipeline, and continued to retreat until the first half of the scour process ended. In the second half of the scour process, the sediment transportation occurred in a similar but mirror-imaged manner. The scour hole propagation rate was also determined based on visualization. The results show that the scour hole propagation rate under a pipeline decreases with an increasing pipeline embedment ratio and rises with the KC (Keulegan–Carpenter) number, which is similar to the result of a previous study.